Multi—Proxy Reconstructions of Climate Change and Human Impacts Over the Past 7000 Years From an Archive of Continental Shelf Sediments off Eastern Hainan Island, China - Huang, Chao; Kong, Deming; Chen, Fajin; Hu, Jianfang; Wang, Peng; Lin, Junchuan (Frontiers in Earth Science, 2021)
Abrupt climatic events and the history of human activities on Hainan Island are poorly understood, due to the lack of high-resolution records. We present high-resolution multiproxy records from the coastal shelf off eastern Hainan Island in China to investigate abrupt climate change and regional human–environment interaction over the last 7000 years. A prominent climatic anomaly occurred during 5400–4900 cal yr BP. This abrupt monsoon failure has been detected in various paleoclimatic records from monsoonal regions. Anomalous summer monsoon intensity during 5400–4900 cal yr BP is probably driven by solar variability, ENSO activity and ice-rafting events in the North Atlantic. Over the past 1500 years, with the growing population and progress in production technology, human activity has increasingly become the dominant factor controlling the natural environment of Hainan Island.